2020
DOI: 10.12688/f1000research.20704.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between postpartum depression and lactation status at a Japanese perinatal center: A cross-sectional study

Abstract: Some studies have demonstrated that breastfeeding can Background: protect mothers from postpartum depression; therefore, we examined the association between postpartum depression and lactation status at one month after delivery at a Japanese perinatal center.We reviewed the obstetric records of all (total 809) nulliparous Methods: healthy women with vaginal singleton delivery at 37-41 weeks' gestation at our institute between July 2018 and June 2019. A face-to-face interview with the women was conducted on adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Low occurrence of breastfeeding and low birth weight were shown to be risk factors for postpartum depression . Although breastfeeding can protect individuals from postpartum depression, it was not found to be associated with incomplete breastfeeding in some studies, and there were other risk factors for postpartum depression . In the early postpartum period, mothers and infants navigate a critical neuroendocrine transition from pregnancy to lactation, and the shared neuroendocrine mechanism is hypothesized to contribute to both lactation failure and perinatal mood disorders .…”
Section: Discussionmentioning
confidence: 68%
“…Low occurrence of breastfeeding and low birth weight were shown to be risk factors for postpartum depression . Although breastfeeding can protect individuals from postpartum depression, it was not found to be associated with incomplete breastfeeding in some studies, and there were other risk factors for postpartum depression . In the early postpartum period, mothers and infants navigate a critical neuroendocrine transition from pregnancy to lactation, and the shared neuroendocrine mechanism is hypothesized to contribute to both lactation failure and perinatal mood disorders .…”
Section: Discussionmentioning
confidence: 68%
“…Mothers diagnosed with postpartum depression usually delivered children with lower birth weight, which was also confirmed in the present study [ 36 , 37 ]. A similar study conducted in Japan revealed no differences with regards to the intensification of postpartum depression, depending on the form of feeding the child [ 38 ].…”
Section: Discussionmentioning
confidence: 99%